ANALISIS PROFIL PELAJAR PANCASILA DIMENSI BERNALAR KRITIS PADA PEMBELAJARAN MATEMATIKA KELAS IV SDN SIASEM 02 - Eigy Yanuar Tri Dewi; Iin Purnamasari; Fajar Cahyadi (STKIP Subang, 2025)
This study aims to describe the Pancasila Student Profile content in the critical thinking dimension, the implementation of the Pancasila Student Profile in the critical thinking dimension in mathematics learning, and the patterns of critical thinking in mathematics learning in fourth grade. The research subjects include fourth-grade students, school principals, and homeroom teachers. The research method used is descriptive qualitative. Data were obtained through interviews, observations, questionnaires, mathematics questions, and documentation, which were then verified using triangulation techniques to ensure the accuracy of the data. The results of the study indicate that there are three contents of the Pancasila Student Profile, namely, obtaining and processing information and ideas, analyzing and evaluating reasoning, and reflecting on thoughts and thinking processes; the implementation of the Pancasila Student Profile has been reflected in learning activities, as seen from the results of the student questionnaire, which obtained an average percentage score of 61.3% in the good category; and the pattern of critical thinking dimensions in fourth-grade learning was obtained from the sub-elements of asking questions, identifying, clarifying, and processing information and ideas, analyzing and evaluating reasoning and procedures, and reflecting on and evaluating one's own thoughts.